INHERITED DISORDERS OF AMINO ACID METABOLISM: BIOCHEMICAL FOUNDATIONS AND MOLECULAR MECHANISMS - Mahmudova Madina Rasuljon qizi; Shukurlayeva Mehriniso Xayrullo qizi (TADQIQOTLAR, 2025)
Abstract Background: Inborn errors of amino acid metabolism constitute a significant class of genetic disorders that may lead to severe neurological impairment, growth retardation, and systemic dysfunction if not diagnosed and managed promptly. Methods:  A  comprehensive  literature  review  was  conducted,  examining epidemiological data, biochemical mechanisms, diagnostic strategies, and therapeutic approaches related to major inherited amino acid metabolism disorders. Results: Conditions such as phenylketonuria, maple-syrup urine disease, and homocystinuria  exhibit  distinct  biochemical  signatures  enabling  early  detection through newborn screening. Tandem mass spectrometry has substantially improved diagnostic  precision.  Therapeutic  strategies  primarily  include  dietary  restriction, cofactor supplementation, and metabolic detoxification, while emerging modalities—such as gene therapy and enzyme replacement—demonstrate promising potential. Conclusion: Early identification via systematic newborn screening, combined with targeted dietary and pharmacological management, significantly enhances long-term  outcomes.  Future  research  is  directed  toward  molecularly  targeted  therapies, including gene-editing techniques and small-molecule modulators.